Effect of different levels of berseem supplementation in donor animal diet on in vitro dry matter digestibility and gas production of wheat straw - Das, Asit; Singh, G P (The Indian Journal of Animal Sciences, 2012)
Wheat straw was incubated with rumen fluid collected from cattle led on either wheat straw alone (OB), or wheat straw supplemented 15 (15B), 30(30B), or 45% (45B) of berseem on DM basis. In vitro dry matter digestibility (IVDMD), organic matter digestibility (IVOMD) and gas production (UP) were studied. IVDMD was 38.06, 42.07, 44.56 and 44.59%; IVOMD was 40.25, 44.08, 45.83 and 47.75% and GP (ml/0.5g substrate) was 39.1, 40.6, 46.2 and 42.8 in groups OB, 15B, 30B and 45B respectively. IVDMD, IVOMD and GP increased significantly (P